Review of the Disparity of Judges' Decisions in Cases Narcotics Abuse - Vicki Dwi Purnomo; Aida Dewi (Indonesian Journal of Economic & Management Sciences, 2023)
Criminal disparity is unequal sentencing which is dangerous in nature compared to without a clear justification. Judge's decision in juvenile criminal cases, in practice there is a disparity in sentencing. Therefore, the issue of sentencing is not only important for judges and the judicial process, but also for the legal process as a whole, especially in terms of law enforcement. Where in this case raises different criminal penalties among the children of the perpetrators of these crimes. Decision disparity cannot be separated from the judge's discretion to impose a sentence in a criminal case. a case. The approach to be used is a Juridical Sociological approach